2015
DOI: 10.4236/jbise.2015.89055
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bone Screw Configurations on the Interfragmentary Movement in a Long Bone Fixed by a Limited Contact Locking Compression Plate

Abstract: The locking compression plates (LCP) are efficient tools in open reduction and internal fixation (ORIF), especially in osteoporotic bones. Two important factors of screw density and screw position can affect the functionality of the bone plate. Several studies have assessed the influence of the screw configurations on the bone-plate stiffness, but the effects of screw positions on the interfragmentary strain, εIF of LCP construct have not been investigated yet. In this study, finite element method was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Furthermore, modulus of elasticity of implant, plate thickness, and screw configuration were found as three dominant physical and mechanical factors, which strongly encourage the secondary healing pathway. These findings are consistent with previous studies which emphasized the individual importance of each of these parameters on bone healing 50,51 …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, modulus of elasticity of implant, plate thickness, and screw configuration were found as three dominant physical and mechanical factors, which strongly encourage the secondary healing pathway. These findings are consistent with previous studies which emphasized the individual importance of each of these parameters on bone healing 50,51 …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the transcortical bone contact modelled in that study would produce high interfragmentary strain, initiating bone resorption at the fracture gap. [35][36][37][38] The consequent gap widening, necessary to reduce interfragmentary strain to levels where fibrous tissue could begin to form, could be expected to prolong fracture healing and promote further plate deformation. In such a situation, successful healing could only occur if fracture biology in that case was powerful enough to produce a healing time that was within the fatigue life and capacity of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [11] used FEM to explore the distributions of different threaded holes on the locking plate, but different configurations of the screws were not studied. Nourisa et al [12] used FEM to investigate the influence of screws number and position on the interfragmentary strain of LCP-femur system for a midshaft fracture. Heyland et al [13] found that semirigid screws could change plate working length to control interfragmentary movement for locking plate fixation at the distal femur.…”
Section: Introductionmentioning
confidence: 99%